Answer :


[R1’ = R1 + R2 + R3]


[R1’ = R1/2]


[R1’ = R1 - R2 & R2’ = R2 - R3]


= 2[c{a(a + b) - ( - ac)} + 0 + a{c(b - c) - ac}] [expansion by first row]


= 2(a2c + abc + ac2 + abc - ac2 - a2c)


= 4abc


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Using properties Mathematics - Board Papers

Prove the followiMathematics - Board Papers